2017
DOI: 10.1111/jcmm.13118
|View full text |Cite
|
Sign up to set email alerts
|

CD44+ fibroblasts increases breast cancer cell survival and drug resistance via IGF2BP3‐CD44‐IGF2 signalling

Abstract: CD44, a cell adhesion protein, involves in various process in cancer such as cell survival and metastasis. Most researches on CD44 in cancer focus on cancer cells. Recently, it is found that CD44 expression is high in fibroblasts of tumour microenvironment. However, its role in communication between fibroblasts and breast cancer cells is seldom known. In this study, CD44‐positive (CD44+Fbs) and CD44‐negative carcinoma‐associated fibroblasts (CD44−Fbs) were isolated and cocultured with breast cancer cells for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…By regulating Lin28, HMGA2, CD44, IGF2, and IGF1R, IGF2BP3 increases cell survival and resistance to conventional and targeted drugs in several tumors. In particular, by affecting IGF2 and/or IGF1R expression, IGF2BP3 has been shown to modulate sensitivity to anti-IGF1R agents (Liu et al, 2017;Panebianco et al, 2017;Mancarella et al, 2018a) and MAPK/PI3K inhibitors (Suvasini et al, 2011). Moreover, IGF signaling modulation is thought to be responsible for the association between IGF2BP3 expression and radio-resistance in chronic myeloid leukemia and squamous cell esophageal cancer (Liao et al, 2011;Yoshino et al, 2014).…”
Section: Effects Of Igf2bp3 On Tumor Progressionmentioning
confidence: 99%
“…By regulating Lin28, HMGA2, CD44, IGF2, and IGF1R, IGF2BP3 increases cell survival and resistance to conventional and targeted drugs in several tumors. In particular, by affecting IGF2 and/or IGF1R expression, IGF2BP3 has been shown to modulate sensitivity to anti-IGF1R agents (Liu et al, 2017;Panebianco et al, 2017;Mancarella et al, 2018a) and MAPK/PI3K inhibitors (Suvasini et al, 2011). Moreover, IGF signaling modulation is thought to be responsible for the association between IGF2BP3 expression and radio-resistance in chronic myeloid leukemia and squamous cell esophageal cancer (Liao et al, 2011;Yoshino et al, 2014).…”
Section: Effects Of Igf2bp3 On Tumor Progressionmentioning
confidence: 99%
“…Some are related to drug resistance in speci c subtypes. Disease progression and drug resistance are commonly associated with poor overall survival due to the uncontrollable nature of cancer cells [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…33 CD44 is highly expressed in cancer cells and cancer-associated ECs, 3,[34][35][36] and its expression has been observed to be associated with poor prognosis for many cancer types, including colorectal carcinoma, infiltrating ductal carcinoma, gastric adenocarcinoma, bladder cancer, head and neck cancer. [37][38][39][40][41][42][43] Although CD44 is widely recognized as a cancer stem marker 3,44 and promotes cancer progression and metastasis by regulating cancer cell stemness, 3,44,45 survival, [46][47][48] proliferation, [47][48][49] and adhesive and invasive properties, [50][51][52][53] the protumorigenic effects of CD44, at least partially, rely on its tumor angiogenesis-promoting activities. 25 A number of studies have revealed a positive relationship between CD44 expression and microvessel density (MVD), which is a characteristic of angiogenesis, in human tumor samples.…”
Section: Cd44 In Tumor Angiogenesismentioning
confidence: 99%